Cytotoxic triterpenoids from the bark of Aglaia smithii (Meliaceae) - Awang, Khalijah; Harneti, D.; Tjokronegoro, R.; Safari, A.; Supratman, U.; Loong, X.M.; Mukhtar, M.R.; Mohamad, K.; Hayashi, H. (Elsevier, 2012)
Two new dammarane triterpenoids, aglinone (1) and aglinin E (20S,24S-epoxy-25-hydroxy-1-en-dammarene) (2) along with three known compounds, 3-epiocotillol (3), aglinin A (4), and eichlerianic acid (5), were isolated from the bark of Aglaia smithii. The chemical structures of the new compound were elucidated on the basis of spectroscopic data interpretation. All the compounds isolated were evaluated for their cytotoxic effects against P-388 murine leukemia cells. Compounds 1, 2, 4 and 5 showed cytotoxicity against P-388 murine leukemia cells with IC50 values of 21, 42, 34, and 11 μg/mL, respectively.